2018
DOI: 10.1090/tran/7277
|View full text |Cite
|
Sign up to set email alerts
|

The dancing metric, ${G}_2$-symmetry and projective rolling

Abstract: The "dancing metric" is a pseudo-riemannian metric g of signature (2,2) on the space M 4 of non-incident point-line pairs in the real projective plane RP 2 . The null-curves of (M 4 , g) are given by the "dancing condition": the point is moving towards a point on the line, about which the line is turning. We establish a dictionary between classical projective geometry (incidence, cross ratio, projective duality, projective invariants of plane curves. . . ) and pseudo-riemannian 4-dimensional conformal geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 25 publications
(131 reference statements)
0
29
0
Order By: Relevance
“…Our initial motivation for this article is twofold. Firstly, it is an extension of the observation made in [7] where, inspired by the rolling problem of Riemannian surfaces [6], a notion of projective rolling was defined which gives rise to (2,3,5)-distributions. Consequently, it was observed that the (2,3,5)-distributions whose algebra of infinitesimal symmetries is maximal i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial motivation for this article is twofold. Firstly, it is an extension of the observation made in [7] where, inspired by the rolling problem of Riemannian surfaces [6], a notion of projective rolling was defined which gives rise to (2,3,5)-distributions. Consequently, it was observed that the (2,3,5)-distributions whose algebra of infinitesimal symmetries is maximal i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Proposition 2. 7 An almost para-Hermitian structure (M, g, K ) is para-Kähler if and only if 1 4 = 0 and 4 1 = 0, in one (and therefore any) adapted coframe. As a result, the Levi-Civita connection form of g is reduced to…”
Section: Pk Structures In An Adapted Coframementioning
confidence: 99%
See 1 more Smart Citation
“…This construction encapsulates the configuration space of 2 surfaces rolling along one another without slipping and twisting. The authors in [5] then found new examples of flat (2, 3, 5)-distributions that arise from rolling bodies, prompting further search in [8]. The solutions to (1.2) give examples of 4-dimensional split signature metrics that have their An-Nurowski twistor distributions having split G 2 as its group of symmetries and we exhibit them in Section 7.…”
Section: Introductionmentioning
confidence: 91%
“…If ε = 1, CL 4 → L 4 can be identified with the subbundle of the twistor bundle whose fiber over a point x ∈ L 4 comprises all self-dual 2-planes in T x CL 4 except the eigenspaces of the endomorphismK x . The total space CL 4 carries a tautological rank 2-distribution obtained by lifting each self-dual totally isotropic 2-plane horizontally to its point in the fiber, and it was observed [2,6] that, provided the self-dual Weyl tensor of the metric on L 4 vanishes nowhere, this distribution is (2, 3, 5) almost everywhere. This suggests a relation of the present work to the An-Nurowski twistor construction (and recent work of Bor and Nurowski).…”
Section: The ε-Kähler-einstein Fef Ferman Constructionmentioning
confidence: 99%